Zainuddin Of Freedoom Fighters At Lubuk Minturun 1945-1950 - Wahyuni Nandira, Adhella - (Pendidikan Sejarah, 2014)
The written is stuch as study of thematic biography which described about a Hero whose name was Zainuddin in that time. The battle of Zainuddin was known as patriot will be researched properly, because it is concerned with his history as a Hero. The issues will study a bout Zainuddinâs Biography before he became a soldier and his function in defend Indonesiaâs Independent in Lubuk Minturun West Sumatera. The aim of this research is to describe Zainuddin play of role in defend Indonesian Nagari Lubuk minturun. The method that used in this research is History methods which is doing in some steps. First, Heuristik is collecting data that relevan as well as studying library in spite of. Interview in studying library, the writer gets lesson from some books and scholarly paper about History, and also interview has dome with some figures who knows about Zainuddin battle. the second part is, critical sources, means data test through both critical Internal and external. And the third one is Interprestation data. And also the fourth step is, Historiography provides in thesies from. The result of this research showed that Zainuddin was born from educated family with high etnic value and religy in this village. Zainuddin entered school which built by Dutch namedâ Proclamasi Indonesiaâsâ school when Indonesia, Dutch wanted to colonize Indonesia especially â Lubuk Minturun Regionâ in â Koto Tangahâ Zainuddin had participate become a member of â BKR ( Badan Keamanan Rakyat) who guided by Aji Lakon. Then he followed to investigated soldier of Dutc in some region like Koto Tangah region, Pauh and Tabing Linggar Jati Area and then Zainuddin was believed by Captain Aji Lakon to become a leader group I and Followed to recruit his comrade and colleague to against soldiers of Ducth in the Batang Anai with gerilya to get out the colonial, Dutch.